Ford Building at 15 Ashburton Place, July 1961 - Unknown (Tufts Archival Research Center, 2005)
Street-level view north-northwest of the Ford Building, located at 15 Ashburton Place at the northeast corner of Ashburton Place and Bowdoin Street. The facade of the building faces south-southeast. Two people get into an automobile parked on Bowdoin Street and Ashburton Place. 3 1/16 x 3, 3 5/16 x 3 1/4 overall Photographs